Revisar o passado e negar a história: o meme como uso político do passado pela extrema-direita - Gallindo, Dora de Sá (2023)
Faced with a scenario of disputes over narratives that idealize, misrepresent, falsify and deny the recent dictatorial past through contemporary media, this research has a double objective. Initially, I analyzed the political uses of the past and the idea of the Brazilian Military Dictatorship (1964-1985) in internet memes, specifically those that convey revisionist, denialist and history-falsifying approaches. Then, I built a workshop class focused on the work of History teachers with such memes in the classroom. To do so, I resorted to Jörn Rüsen's theory of historical consciousness (2001), which considers historical learning as a process that occurs in different means of socialization. Hence the need to investigate the social circulation of historical knowledge (CERRI, 2010) and the temporal orientation underlying socially disseminated historical ideas (SADDI, 2014), as defended by the Didactics of History. Another axis of theoretical-methodological support is based on the contributions of Historical Education, especially from authors such as GERMINARI (2011), BARCA (2001, 2005), GAGO (2020) and LEE (2001). The objectives in question were achieved from the analysis of memetic pieces as historical sources, whose narratives were verified from the Content Analysis methodology through a qualitative bias, as well as through interpretation strategies elaborated by Silvio Cadena (2018). In turn, the workshop class was built based on the methodology proposed by Isabel Barca (2018). Throughout the research, I was able to observe how the analyzed memes produce rehabilitating and apologetic versions of the Military Dictatorship. Worryingly, such political use of the past does a lot of harm. One of them is the promotion of practices of disinformation and political-ideological manipulation, considering that such media convey intentionally produced false information. As a result, I observed the damage to the contemporary democratic order. That is why it is important for historians to understand this process and act both in classrooms and in other spaces of socialization based on historical criticism in the interpretation of the experience of time in order to reveal and avoid the abusive use of the past.